Study of diurnal and seasonal variations in the time series data of soil 222Rn gas. Issue 3 (19th February 2021) - Tareen, Aleem Dad Khan; Rafique, Muhammad; Basharat, Muhammad
ABSTRACT: The diurnal and seasonal variation study has been performed for soil radon time series (RTS) data obtained using RTM-1688 radon monitor (SARAD GmbH, Dresden, Germany). Data were collected from radon station installed at latitude 34.39621 and longitude 73.47347 on fault line passing beneath the Muzaffarabad city, for a period of 1 year. RTS data were analysed based upon their monthly recorded values followed by an interpretation of season-wise data, based upon 10-day measurements, in order to get more insight into radon variations. Minimum value of 1.3553 × 10 4 Bq m −3 was recorded for the first 10 days of the month of March 2017, whilst maximum value 2.7902 × 10 4 Bq m −3 was recorded from 8th to 17th day of August 2017. Overall mean value for RTS data were found to be (2.1024 ± 0.2088) × 10 4 Bq m −3 . Data obtained for the current study show that the variations observed in the season of spring are comparatively smaller in magnitude than the other three seasons. Month-based correlation between soil radon gas with environmental parameters has also been investigated for the entire study period. For the months starting from March to September, a positive correlation of radon in soil with the relative humidity and pressure has been observed while no significant correlation was found between radon in soil and temperature for these months. For October to December 2017, the soil radon gas was mainly influenced by temperature variations and almost the same pattern was observed for the months of January and February with additional impact coming from pressure. The current study findings can be used as an indicator for some applications, viz., seismic activity, location of subsurface faults, indoor radon concentration and uranium exploration.